Norma Kultural dalam Gending Rarè Bangun Semengan (Analisis Semiotika) - Komang Wahyu Rustiani; I Gusti Made Swastya Dharma Pradnyan; Rahmat Sewa Suraya; Ni Made Ayu Susanthi Pradnya Paramitha (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
The Balinese people possess a whole range of custom and tradition in nurturing children since their early ages. One of these traditions appeared through song and called as gending rarè. For many years, Gending rarè believed for its in-depth cultural meaning. This study will analyze this practice by using semiotics’ theory. Gending rarè entitled bangun semengan encompasses norms of Balinese people which gets dominant Hinduism teaching values namely Tri Hita Karana. Throughout this song, children in Bali are exerted to preserve their environment, their cleanliness either by spirituality or physically and also to establish harmonious relationship in their family and society. Moreover, Children are encouraged to apply the teaching of palemahan and pawongan prior to the Parhyangan values.